Improved titanium dioxide promoted photocatalyst for degradation of pollutant in water / Emy Marlina Samsudin - Emy Marlina, Samsudin (2016)
The quality of drinking water is testified to be satisfactory in most developed countries. However, the United Nations has reported that 783 million people do not have access to safe drinking water. Furthermore, only 1% of available water resources can be used as drinking water. One of the most common pollutants found in drinking water is atrazine herbicide. Malaysia, being an active player in agriculture consumes large quantity of atrazine and other pesticides. Atrazine is classified as low toxic herbicides but prolong consumption leads to cardiovascular and mutagenic effects. The current technology is via granulated activated carbon (GAC) however it leads to leaching, non-selective and waste disposal costs. An alternative effective method is by photocatalytic degradation using semiconductor photocatalyst. The key factor for a successful photocatalytic activity is to sustain large concentrations of surface active radicals to oxidize pollutants into simpler and less hazardous substance. In photocatalysis, TiO2 is a preferred semiconductor as it is cheap, photo-active, stable and is non-toxic. However, the photocatalytic ability of TiO2 is limited to only a small fraction of solar light (4%) and hence hampers its activity. Numerous efforts are initiated to improve TiO2 properties which include anion doping and most recent hydrogenation of TiO2. Nevertheless, the photocatalytic activity of anion-doped TiO2 was only accessible under UV and visible light. In addition, hydrogenated TiO2 was reported to possessed rapid electrons and holes recombination although the optical response was extended towards the infra-red region. In this work, hydrogenated F-doped TiO2 showed remarkable enhancement for the photocatalytic degradation of atrazine by a factor of ~8.5 relative to as prepared TiO2. Within 180 min of photocatalytic activity, more than 95 % of 0.5 mg/l atrazine was removed. Atrazine removal was shown to exceed those of N,F co-doped TiO2 (85